PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE HUMANISTIS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS 8C DI SMP AHMAD YANI KOTA BATU - Yusfia Arifatul Azizah; Ach. Faisol; Indhra Musthofa (VICRATINA, 2022)
Education is the process of each individual making choices regarding the direction of the road to achieve his life goals. Of course this is every god's creature in the world, especially humans and their civilizations have different life goals. It is in these different goals that there must be special expertise in the fields of science, pedagogy or education, and teaching to students who in our country are referred to as "Teachers". Every student of knowledge through the teacher, they really need the fulfillment of personal needs that can make it easier for them to face global challenges in a life that is always changing automatically from one period to the next. The purpose of this study was to determine the application of the humanistic method to improve student learning outcomes in class VIII in PAI learning at Ahmad Yani junior high school Batu City, to determine the improvement in student learning outcomes in PAI learning through humanistic methods in class VIII at Ahmad Yani junior high school Batu City. This research was conducted at Ahmad Yani Junior High School, Batu City. The method used in this research is classroom action research. The type of CAR in this study is Experimental CAR, with Kurt Lewin's Model which has two cycles. Each cycle has four stages, including Planning, Implementation, Observation, and Reflection. The data of this study were obtained through observation, interviews, documentation, and evaluation. The results of the study showed the results of the evaluation of student learning in the pre-cycle, cycle I and cycle II which displayed the value that became the completeness of student learning outcomes. The minimum completeness criteria (KKM) in grade 8C of SMP Ahmad Yani is 70. It is known that all of them achieved the KKM score. The percentage of learning outcomes in the pre-cycle is 70.5, the first cycle is 86.7 better than before. Meanwhile, in the second cycle, the score was 92.10417. In this study, the author states that it can be used as a recommendation and reference for further research and can be used for educators using the humanity method.Keyword : Humanistic, Learning Outcomes, Islamic Education and Morals